Moving Up or Falling Behind? Gender, Promotions, and Wages in Canada - Mohsen Javdani; Andrew McGee (Institute for the Study of Labor (IZA), 2015)
We estimate gender differences in internal promotion experiences for a representative sample of Canadian workers using linked employer-employee data. We find that women in Canada are 3 percentage points less likely to be promoted and have received fewer promotions than similar men, but these differences stem almost entirely from gender differences in industry and occupation. By contrast, women experience an estimated 2.9 percent less wage growth in the year of a promotion than similar men even after controlling for industry, occupation, and firm effects – though a significant "family gap" exists among women as single women and women without children experience essentially the same wage returns to promotion as men.
Keywords: J16; J31; J62; J71; 330; promotions; gender wage gap